2017
DOI: 10.1186/s13568-017-0483-1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CsLEA11, a Y3SK2-type dehydrin gene from cucumber (Cucumis sativus), enhances tolerance to heat and cold in Escherichia coli

Abstract: As the group II LEA (late embryogenesis abundant) proteins, dehydrins (DHNs) play an important role in plant growth and development, as well as in response to abiotic or biotic stress challenges. In this study, a DHN gene named CsLEA11 was identified and characterized from Cucumis sativus. Sequence analysis of CsLEA11 showed that it is a Y3SK2-type DHN protein rich in hydrophilic amino acids. Expression analyses revealed that the transcription of CsLEA11 could be significantly induced by heat and cold stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…In this study, it was found that DHNs not only act as drought-resistant protein, but also interact with FK506 binding protein in the nucleus and acts as regulatory protein for drought tolerance by regulating the ABA responsive signaling pathway (Tiwari et al, 2019). DHNs have been recognized as molecular protectors for functionality of some proteins such as lactate dehydrogenase and malate dehydrogenase in response to environmental stresses, as supported by previous studies (Zhou et al, 2017;Lv et al, 2018). Misfolding of proteins that are toxic to plants is triggered by drought stress, so protein quality control is critical to plant quality.…”
Section: Dhns and Other Proteins' Interactionssupporting
confidence: 64%
“…In this study, it was found that DHNs not only act as drought-resistant protein, but also interact with FK506 binding protein in the nucleus and acts as regulatory protein for drought tolerance by regulating the ABA responsive signaling pathway (Tiwari et al, 2019). DHNs have been recognized as molecular protectors for functionality of some proteins such as lactate dehydrogenase and malate dehydrogenase in response to environmental stresses, as supported by previous studies (Zhou et al, 2017;Lv et al, 2018). Misfolding of proteins that are toxic to plants is triggered by drought stress, so protein quality control is critical to plant quality.…”
Section: Dhns and Other Proteins' Interactionssupporting
confidence: 64%
“…In addition, this phenomenon is also associated with variation in temperature [ 43 ]. Lactate dehydrogenase (LDH) is widely used in dehydrin cryoprotective assays [ 7 , 9 , 16 , 44 , 45 ]. It has been reported that K2 and YSK2 dehydrin were able to protect LDH activity better than BSA.…”
Section: Molecular Structure Of Dehydrinsmentioning
confidence: 99%
“…Evidence from many studies has revealed a strong association between dehydrins and plant tolerance to heat stress. For instance, dehydrin CsLEA11 and WZY2 proteins were able to protect both recombinant E. coli and activity of the LDH enzyme under heat stress [ 9 , 16 ]. Dehydrin DHN-5 from wheat was found to play a relevant role in protecting enzyme β-glucosidase (bglG) against heat stress.…”
Section: The Regulation Of Dehydrin Genes Under Abiotic Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted on the hardy plant Prunus mume showed that five dehydrin genes from P. mume ( PmLEA8 , PmLEA10 , PmLEA19 , PmLEA20 , and PmLEA29 ) could enhance E. coli tolerance to salt and sorbitol stresses ( Bao et al, 2017 ). A Y 3 SK 2 -type dehydrin gene from cucumber ( Cucumis sativus ), CsLEA11 , could also enhance tolerance to high or low temperature when overexpressed in E. coli ( Zhou et al, 2017 ). Our research demonstrated that GST-IpDHN can be easily and obviously induced in E. coli BL21 ( Figure 3A ), and the spot assay, single clone counting assay, and cell growth curves of E. coli showed that IpDHN could significantly enhance salt/drought and sorbitol tolerance of E. coli cells ( Figure 3B and Supplementary Figures S4A,B ).…”
Section: Discussionmentioning
confidence: 99%